Effects of Bifidobacterium bifidum tetragonum tablets and Jin Gui Ren Qi Pill on intestinal flora and metabolism in patients with diabetic kidney disease - Zhang, Cheng-Yu; Yue, Dong-jie; Wang, Di; Wu, Fei-fei (Frontiers in Pharmacology, 2024)
To investigate the effects of Bifidobacterium bifidum tetragonum tablets and Jin Gui Ren Qi Pill on intestinal flora and metabolism in patients with diabetic kidney disease.In the study conducted at Heping Hospital of Changzhi Medical College from March 2021 to December 2022, 30 cases of patients diagnosed with diabetic nephropathy were meticulously selected as study subjects. Employing a double-blind randomized table method, these patients were randomly allocated into three groups: the control group (n=10), the Bifidobacterium bifidum tetragonum tablets group (n=10), and the Jin Gui Ren Qi Pill group (n=10). The control group received standard western medical treatments for diabetic nephropathy, including serum glucose, blood lipids, blood pressure management, and other conventional therapies. In addition to the standard treatments, the Bifidobacterium bifidum tetragonum tablets group received Bifidobacterium bifidum tetragonum tablets, while the Jin Gui Ren Qi Pill group received Jin Gui Ren Qi Pill. Before and after a 4-week treatment period, various baseline parameters were assessed, including fasting blood glucose (FBG), two-hour postprandial blood glucose (2hPBG), triglycerides (TG), serum total cholesterol (TC), serum low-density lipoprotein cholesterol (LDL-C), serum high-density lipoprotein cholesterol (HDL-C), random urine microalbumin/creatinine ratio (ACR), blood creatinine (SCr), and traditional Chinese medicine (TCM) evidence scores. Stool specimens were collected from all three groups before and after treatment for 16S rDNA high-throughput sequencing, followed by comprehensive analyses including OUT clustering, Alpha diversity, Beta diversity, species composition analysis, LEfSe analysis, and KEGG function prediction. Spearman correlation analysis was employed to explore the relationship between intestinal flora and clinical indicators. Furthermore, fasting peripheral venous blood was collected from patients in the Bifidobacterium tetrapunctate tablets group and the control group before and after intervention to measure the OD values of tumor necrosis factor-α (TNF-α),